A Study of Women Workers' Safety and Achievement at the Workplace with Particular Reference to Rampur Town (Ranchi District): Examining Women Workers' Safety and Achievement in Rampur Town (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Women in the working who earn money or a salary are part of a modern phenomenon, one thatoccurred at the same time as the expansion of paid employment for males yet, women continue to facechallenges in the workforce due to inequality. The vast majority of businesses did not provide a secureenvironment in which women could carry out their jobs without incident. The firm ought to have effectiveprocedures in place for managing its human resources. This is evident in the prejudice that existsbetween male and female workers in terms of pay scale, job security, higher designations, and otheraspects of employment. Workplaces are not safe places for women. But as things are right now, everyorganisation has a responsibility to play a significant part in the advancement of women in the workforcewithin the firm. The ethical conduct of a company includes providing women with equal opportunities.All rights, including those that will protect women workers' interests in the workplace, will be extendedto female employees. The purpose of this study is to provide information about the safety of femaleemployees in the workplace as well as their performance. The basic data for this study came fromsurveys and interviews with residents of Rampur Town ( Ranchi ), which is located in the state ofJharkhand.